Conservation concept for the treatment of biologically induced encrustations and formation of tufa - Martina Haselberger (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The sculpture of the eastern Naiad Fountain at Schönbrunn made of white marble is covered with calcareous encrustations and secondary grown tufa. These biologically induced accretions influence its actual appearance significantly. Examinations of structure and composition of the crusts and tufa, and the inhabiting organisms responsible for the precipitation, as well as, considerations of historic issues enable the development of a concept for the conservation.